2013
DOI: 10.2147/jbm.s42211
|View full text |Cite
|
Sign up to set email alerts
|

Lipid profile of regular blood donors

Abstract: IntroductionA few reports have linked regular blood donation to the lowering of parameters of lipid profile. Estimating the lipid profile is an accepted method of assessing an individual’s risk for coronary heart disease, particularly if there is evidence of lipid peroxidation. Regular blood donation may lower iron stores, and this in turn lowers lipid peroxidation. This study was carried out to determine the effect of blood donation on lipid profile.Materials and methodsEighty-two participants consented to pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 13 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…This may be associated with the risk of cardiovascular disease reported by some authors, as well as with the oxidative changes caused by iron [11] . Regular blood donation may be protective against cardiovascular disease as reflected by significantly lower mean total cholesterol and low-density lipoprotein levels in regular blood donors than in non-donors [12] . Endothelial dysfunction, secondary to systemic inflammation and oxidative stress, is known to play a major role in the development and progression of atherosclerosis.…”
Section: Discussionmentioning
confidence: 97%
“…This may be associated with the risk of cardiovascular disease reported by some authors, as well as with the oxidative changes caused by iron [11] . Regular blood donation may be protective against cardiovascular disease as reflected by significantly lower mean total cholesterol and low-density lipoprotein levels in regular blood donors than in non-donors [12] . Endothelial dysfunction, secondary to systemic inflammation and oxidative stress, is known to play a major role in the development and progression of atherosclerosis.…”
Section: Discussionmentioning
confidence: 97%
“… 20 It was shown that phlebotomy will reduce body iron stores, lower blood pressure, and reduce the risk of developing hyperglycemia and cardiovascular diseases, characteristics most often associated with obesity. 21 People with higher BMI, advanced age, and low physical activity tend to show unfavorable plasma lipid profile that may predispose them to cardiovascular diseases. Thus, obese people may have greater inclination to donate blood because of these benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Our study population was relatively healthy, with respect to both blood lipid levels and physical activity, which is probably the result of donor selection based on eligibility criteria and self-selection [5356]. Beneficial effects of repeated blood donation on blood lipid profiles have been suggested in the literature [57, 58]. However, in these studies, active donors were compared with new and former donors [57, 58].…”
Section: Discussionmentioning
confidence: 99%
“…Beneficial effects of repeated blood donation on blood lipid profiles have been suggested in the literature [57, 58]. However, in these studies, active donors were compared with new and former donors [57, 58]. As such, self-selection of donors may have caused considerable confounding.…”
Section: Discussionmentioning
confidence: 99%